2012
DOI: 10.1002/cne.23007
|View full text |Cite
|
Sign up to set email alerts
|

Sensillum‐specific, topographic projection patterns of olfactory receptor neurons in the antennal lobe of the cockroach Periplaneta americana

Abstract: In vertebrates and many invertebrates, olfactory signals detected by peripheral olfactory receptor neurons (ORNs) are conveyed to a primary olfactory center with glomerular organization in which odor-specific activity patterns are generated. In the cockroach, Periplaneta americana, ORNs in antennal olfactory sensilla project to 205 unambiguously identifiable antennal lobe (AL) glomeruli that are classified into 10 glomerular clusters (T1-T10 glomeruli) innervated by distinct sensory tracts. In this study we em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 70 publications
(149 reference statements)
1
65
0
2
Order By: Relevance
“…Segregation of axon terminals between type1 and type2 PNs was observed in all dual intracellular staining specimens ( n = 5). In previous cockroach studies, OSNs in antennal perforated basiconic sensilla were reported to terminate specifically in the antero-dorsal group glomeruli, whereas those in the trichoid and grooved basiconic sensilla terminated in postero-ventral group glomeruli ( Figure 2E ; Watanabe et al, 2012b). Thus, type1 and type2 PNs appear to receive sensory inputs from different types of antennal sensilla ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…Segregation of axon terminals between type1 and type2 PNs was observed in all dual intracellular staining specimens ( n = 5). In previous cockroach studies, OSNs in antennal perforated basiconic sensilla were reported to terminate specifically in the antero-dorsal group glomeruli, whereas those in the trichoid and grooved basiconic sensilla terminated in postero-ventral group glomeruli ( Figure 2E ; Watanabe et al, 2012b). Thus, type1 and type2 PNs appear to receive sensory inputs from different types of antennal sensilla ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 71%
“…(E) Schematic drawing of parallel pathways from the periphery to higher brain center in the cockroach brain. OSNs in perforated basiconic sensilla ( single-walled A [ sw -A] and sw -B) selectively terminate in antero-dorsal group glomeruli (AD glomeruli), whereas those in trichoid sensilla ( sw- C) and grooved basiconic sensilla ( double-walled A [ dw -A]) projects to the postero-ventral group glomeruli (PV glomeruli: Watanabe et al, 2012b). Therefore, type1 PNs with dendrites in PV glomeruli and type2 PNs with dendrites in AD glomeruli form two segregated parallel pathways from the periphery to higher brain centers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations